ANIMATING VALUES: EXPLORING METHODS OF INSTILLING RELIGIOUS AND MORAL PRINCIPLES IN EARLY CHILDHOOD THROUGH ANIMATED SERIES - Partono, Partono; Ahmadi, Ahmadi (PIAUD Universitas Islam Negeri Sunan Kudus, 2024)
Religious and moral values are considered one of the most important aspects of a child's development. Gaining information about the methods or practices used to instill these values can be beneficial for early childhood education. This research aims to describe the methods of instilling religious and moral values in early childhood through animated film series. Using a qualitative research approach with a postpositivist paradigm, this study employs a case study methodology as its primary approach. Data collection was conducted through three methods: interviews, observations, and documentation. The data analysis approach includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that there are four methods for instilling religious and moral values in early childhood through animated film series. These methods include habituation, exemplification, reinforcement, and the combination of theory and practice.